(3cJGH CHbQGW GdPi hLO aj bHQgs - (3CHbQGW GdMcjes
(3ChdgG (B:s
(3bGd CHbQGW (B: (3EPG cGf ai hSW QCS GdeQjV hQe cGdLhRI hdh jNJai aGYde Cfg jehJ Edi CQHYjf jhekG ef Chd eQVg s
(3BNQgG (B:s
(3bGd CHbQGW (B: (3ZPG cGf Nda GdCPGf GdjSQi HKQI ShOGA aGYde Cf UGMHgG jehJ Edi CQHYI hYTQhf jhekG ef eQVI , hBjI Pdc Cfg jTJGb ai Chd eQVI Edi TQH GdeGA GdHGQO JThbkG TOjOkG s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3GfXQg eY OSJhQ GdeHJOFjf Qbe (B464"s
(3hgh NeS hYTQhf eSCdIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B195 s
Keywords: (3GdWHs